Ideais reformatórios abarcados pelo Pietismo que se secularizaram no Iluminismo alemão do século 19 - Felipe de Godoy, Junior (Vox Scripturae - Revista Teológica Internacional, 2012)
There appears to be in the theological midst a profound depreciation of the German Illuminism of the XVIII century, what, in parts, is not licit. As much as it brought together some bad consequences to the theological field, it’s necessary to remember what was the context which made Immanuel Kant “establish” such rational movement. Some time earlier was born in the heart of the Germans the concern towards the neighbor, a concern with a sanctified life. Some time earlier was born, initially through Philip Jacob Spener, the German Pietist Movement (Pietism). The sanctification, amidst all the ideology of the justification approached by the Lutheran Orthodoxy, is prioritized by this movement, as well as the meeting between the human and the divine, which is turned into the center of the being Body of Christ. The present approach tries to verify what both, Pietism and Illuminism, have in common. At a first moment, it presents the Pietist Movement with its representatives and approaches. At a second moment, the approach to the German Illuminism is made. And, on a third moment, the heritage of the Pietism is presented in the outlined Illuminism. It’s concluded that there is between Spener and Kant, between Pietism and Illuminism, much more congruencies than is normally thought.